1995
DOI: 10.1002/jso.2930600206
|View full text |Cite
|
Sign up to set email alerts
|

Expression and loss of heterozygosity of c‐met proto‐oncogene in primary breast cancer

Abstract: The c-met proto-oncogene encodes the receptor to hepatocyte growth factor-scatter factor (HGF-SF), a mesenchyme-derived cytokine with cell-dissociating, invasion, and angiogenic properties. The expression of c-met in breast cancer is the subject of controversy; 111 primary breast cancers were examined for LOH of c-met by Southern blot electrophoresis. c-met expression was measured in a further 40 patients with breast cancer and in 8 patients with benign breast disease by flow cytometry. LOH of c-met was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Interestingly, in these cell lines the expression of Ron inversely correlates with the expression of Met (Stoker et al, 1987;Byers et al, 1994). The data suggesting a role for Met/HGF complex in breast cancer progression are con¯icting (Yamashita et al, 1994;Nagy et al, 1995;Lin et al, 1996;Tuck et al, 1996). Here, we show that another member of the MET family, with similar biological properties, is overexpressed in a large percentage of breast carcinomas.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, in these cell lines the expression of Ron inversely correlates with the expression of Met (Stoker et al, 1987;Byers et al, 1994). The data suggesting a role for Met/HGF complex in breast cancer progression are con¯icting (Yamashita et al, 1994;Nagy et al, 1995;Lin et al, 1996;Tuck et al, 1996). Here, we show that another member of the MET family, with similar biological properties, is overexpressed in a large percentage of breast carcinomas.…”
Section: Discussionmentioning
confidence: 94%
“…The data were normalized and weighted using intensity values (see Materials and Methods). All graphs show the intensity level (2–253) on the x‐axis whereas the y‐axis shows the number of pixels (pc) for each intensity level ( C,I,O,U ), calculated normalized (npc) value ( D, J, P,V ), intensity‐weighted normalized (I*npc) values ( E,K,Q,W ), and square intensity‐weighted normalized (i 2 *npc) values ( F,L,R,X ).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocyte growth factor/scatter factor (HGF/SF), the ligand for Met, is a paracrine pleiotropic factor that can act as a mitogen, morphogen, or motogen for a variety of cells. Met and HGF/SF have been implicated in breast cancer (6–9). Several studies have shown that expression of Met is a strong independent prognostic factor in breast carcinoma (10, 11).…”
mentioning
confidence: 99%
“…We have shown that Met is expressed and activated in normal breast ducts and reduced in some breast tumors (Tsarfaty et al, 1992). On the other hand, Met expression levels were shown to be signi®cantly greater for patients with breast cancer than in benign breast disease (Nagy et al, 1995). Transgenic expression of tpr-met led to development of mammary hyperplasia and tumors (Liang et al, 1996).…”
Section: Introductionmentioning
confidence: 96%